Commitment, Focus, Synergy: The Workplace Forces Cementing the Continuous Quality Improvement - Santiago, Lilia M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Sustaining school effectiveness for accreditation is a big job. There is no better way however for the stakeholders than to accept the challenge because for them, passion to education is priceless. This paper therefore, is presented to evaluate the results of the formal visit conducted by Phil-ippine Association of Colleges and Universities Commission on Accredi-tation (PACUCOA) to the Master of Arts in Education (MAEd) Program of Osias Colleges, Inc. (OCI) Tarlac City. The descriptive research design was utilized involving documentary analysis, questionnaires and check-list. There were three (3) workplace forces: Commitment, Focus and Synergy that were described among the School Accreditation Team (SAT) which revealed that the SAT’s Commitment is positive, Focus is very often and Synergy is good. The compliance to the recommendations of PACUCOA is a self-assessment described as Very Likely which means that OCI has a high degree of compliance. An Action Plan is proposed to enhance quality assurance and level of accreditation, address the weak-nesses and grab opportunities for continuous quality improvement.